2013
DOI: 10.1016/j.jhydrol.2013.08.040
|View full text |Cite
|
Sign up to set email alerts
|

The distributed model intercomparison project – Phase 2: Experiment design and summary results of the western basin experiments

Abstract: Results indicate that in the two study basins, no single model performed best in all cases. In addition, no distributed model was able to consistently outperform the lumped model benchmark. However, one or more distributed models were able to outperform the lumped model benchmark in many of the analyses. Several calibrated distributed models achieved higher correlation and lower bias than the calibrated lumped benchmark in the calibration, validation, and combined periods. Evaluating a number of specific preci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0
13

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 144 publications
(243 reference statements)
3
36
0
13
Order By: Relevance
“…In the phase2 of the Distributed Model Intercomparison Project (DMIP2) (Smith et al 2012(Smith et al , 2013, several distributed models was mixed compared to lumped benchmark, results indicated there was none single model can perform best in all cases. DANUBIA component (Barthel et al 2012) comprised of 17 model components and discussed the integrated simulation of global change influence on agriculture and groundwater.…”
Section: Introductionmentioning
confidence: 99%
“…In the phase2 of the Distributed Model Intercomparison Project (DMIP2) (Smith et al 2012(Smith et al , 2013, several distributed models was mixed compared to lumped benchmark, results indicated there was none single model can perform best in all cases. DANUBIA component (Barthel et al 2012) comprised of 17 model components and discussed the integrated simulation of global change influence on agriculture and groundwater.…”
Section: Introductionmentioning
confidence: 99%
“…While more complex hydrologic models have been developed-fully spatially distributed physically based models were already developed in the 1990s-they are computationally demanding and by some accounts do not demonstrate dramatic improvements in streamflow forecasting skill compared to simpler models (Reed et al 2004;Smith et al 2013). One difficulty for physically based models may be that they attempt to apply physically oriented or empirical laws relevant at fine scales (e.g., soil column infiltration dynamics measurable on the order of 0.1 m) to simulate coarse catchment behavior (e.g., on the order of 1-100 km; Savenije 2009).…”
Section: B Challenge 2: Getting the Numbers Rightmentioning
confidence: 99%
“…In another comparison, Smith et al (2013) concluded that distributed models provided improvements over lumped models in 12-24 % of the cases tested, depending on the criteria of evaluation. The mixed results of these comparisons indicate that lumped models are a good choice when the objectives do not require a distributed model.…”
Section: A J Long: Rrawflow: Rainfall-response Aquifer and Watershementioning
confidence: 99%
“…Although this preliminary version was applied primarily, but not exclusively, to karst, RRAWFLOW is suitable for aquifers and watersheds of any type, and non-karst systems generally are easier to model than karst systems. Convolution, as used in RRAWFLOW, has been applied extensively to non-karst surface-water and groundwater systems (e.g., Nash, 1959;Blank et al, 1971;Delleur and Rao, 1971;Dooge, 1973;Neuman and de Marsily, 1976;Maloszewski and Zuber, 1982;Besbes and de Marsily, 1984;Beven, 1989;Jakeman and Hornberger, 1993;von Asmuth et al, 2002;Reed et al, 2004;von Asmuth and Knotters, 2004;Olsthoorn, 2008;Jurgens et al, 2012;Smith et al, 2013).…”
Section: Rrawflow Overviewmentioning
confidence: 99%